ON THE QUALITY CONTROL OF THE FUEL FILLER FLAP LINING MARK - Monica BÂLDEA; Ancuţa BĂLTEANU; Mihaela ISTRATE (Fiabilitate şi Durabilitate)
The paper provides solutions for the manufacture technological process quality improvement, by implementing a Poka-Yoke device at one of the mold work stations, and by reducing the time required for the manufacturing process by grouping two molds on a single press.